Content Validity and the Reliability of Technological Competency as Caring in The Nursing Instrument_Indonesian Version (TCCNI_IV) - Ignata Yuliati; Ni Luh Agustini Purnama; Sri Winarni (Jurnal Ners, 2019)
Introduction: The TCCNI has not been used to conduct a study in Indonesia previously. The researcher has thus conducted a study on technological competency as a caring in nursing instrument Indonesian version (TCCNI_IV).  This study aims to examine the content validity and reliability of the TCCNI_IV. Methods: An exploratory sequential mixed method research design was used in this study. The researcher used closed-ended question asked of five (5) experts on the content of TCCNI-IV. The researcher explored the expert’s opinion about each statement of TCCNI_IV, and they required suggestions for the statements that were not relevant. Furthermore, the researcher analyzed and rewrote the statements according to the expert’s input. There are twenty-five (25) items in the TCCNI_IV involving technological knowledge and technological caring as an expression of caring in the nursing dimension. Furthermore, the researcher used the TCCNI_IV to gain quantitative data from the 135 nurses in the nursing wards of the hospitals. Based on a finite population of 208 nurses, a total of 135 samples (nurses) participated in the quantitative study. The selection of the participants was through simple random sampling.  There were 135 nurses from the nursing wards in the hospitals (n=135) with experience of at least 1 year in nursing practice. The item content validity (I-CVI) and scale content validity (S-CVI) was tested. The reliability was determined using Cronbach’s alpha α.Results: The “item content validity of the TCCNI_IV ratings ranged from .60 to 1.0. The scale content validity index (S-CVI) was 0.936. The Cronbach’s alpha coefficient of .980 indicates there to be good reliability.Conclusion: The technological competency as a caring in nursing instrument Indonesian version (TCCNI_IV) is thus found to be valid and reliable. It is recommended that the developed instrument needs to be further tested for its reliability and validity in a larger setting.